Espacios de emancipación, propuestas indígenas desde el Ecuador - Soriano Hernández, Silvia (2019)
The indigenous presence in Ecuador is not confined to street demonstrations. From local to national, organized Indians have made proposals that they hope will affect decisions that are taken without consulting them. In order to reflect and appreciate their approaches, I will make a brief tour of the image they express of the nation as a representation, without neglecting the question of racism. I am interested in questioning the idea of modernity as alien to indigenous people, to consider the democracy that characterizes our societies is exclusionary and, finally, approach female militancy to understand the opinions expressed by those who feel a fundamental part of a political structure such as the CONAIE.